A CORRELATIONAL STUDY OF EMPLOYEE SERVICE QUALITY AND CUSTOMER SATISFACTION IN BANKING - Nabila Anastasya; Riny Jefri; Indrawaty Asfah (International Journal of Business English and Communication, 2026)
This study examines the correlation between service quality and customer satisfaction at BRI's Panacan branch, focusing on five key service quality indicators: tangible evidence, responsiveness, assurance, reliability, and empathy. Customer satisfaction is assessed using five factors: overall service quality, meeting customer expectations, repeat usage intention, willingness to refer others, and dissatisfaction. Data analysis using SPSS revealed a robust positive correlation (r = 0.866) between service quality and customer satisfaction, validating the hypothesis that improved service quality enhances customer satisfaction. Significant findings indicate that employee friendliness (a measure of responsiveness) scored 57.8%, while well-maintained facilities, such as ample parking and comfortable waiting areas (a measure of tangible evidence), scored 55.8%, representing the highest scores. Security and reliability were satisfactory but slightly lower, at 50% and 46.8%, respectively. These outcomes align with theories such as SERVQUAL and Expectancy Disconfirmation, which highlight the importance of surpassing customer expectations to achieve satisfaction. Additionally, seamless transactions (50%) positively impact customer satisfaction, reflecting Cognitive Dissonance Theory. The willingness of customers to recommend the bank (42.2%) demonstrates their trust in its services, aligning with Loyalty Theory.In conclusion, this research demonstrates that excellent service quality is essential for enhancing customer satisfaction and loyalty. Continuous improvement is vital to maintaining customer confidence and ensuring the sustained success of banking operations.